The performance of alternative GPS tracking devices: a case report on wild boars (Sus scrofa) - Mervi Kunnasranta; Elmo Miettinen; Markus Melin; Anna Meller; Veli-Matti Väänänen; Otso Huitu; Katja Holmala (Animal Biotelemetry, 2024)
Abstract Background Telemetry studies on terrestrial mammals have been carried out almost exclusively using neck collar-mounted devices. However, collars are not suitable for all species and all age classes and may therefore compromise animal welfare and data quality requirements. Here, we evaluate the use of non-collar tracking devices on wild boars (Sus scrofa), a species for which collars may be problematic due to neck shape and seasonal body mass variation. We tested pelt-glued tags and three types of GPS ear tags. In addition, animals were marked with plain cattle ear tags. Results The tested GPS tags exhibited various technical challenges related mostly to satellite coverage of the study area and tag loss. However, GPS devices enabled moderate movement monitoring of weeks to months, whereas plain cattle ear tags offered information on displacement over longer time intervals. The longest direct dispersal distance (163 km) by a wild boar sounder was discovered by cattle tags. Conclusions Data volume and quality obtained from small tags are inferior to data provided by GPS collars, but low-fix rate tags may enable monitoring of individuals with reduced invasiveness. Moreover, these tags enable tracking in cases where the collar is not an option. The low price and small size of the devices together with technical developments may offer cost-effective tools for future studies on dispersal and survival.